Powers, inequalities and vulnerabilities Impact of globalisation on children, youth and families and on the mission of the church - Vorster, Jakobus (Reformed Theology in Africa Series, 2020)
This research addresses the gap that is present in both missiology and family and youth ministry. Missiology does not focus on children and youth specifically, while this is the largest population in the developing world. On the other hand, family and youth ministry has a more pastoral than missional approach, not always taking cognisance of contexts like globalisation. Thus, the purpose of the book is to address the sometimes unintended and unnoticed influence of globalisation on the mission of the church, with a specific focus on children, youth and family. For this purpose, the International Association for Mission Studies study group for children, youth and families coming from different parts of the world decided to describe the powers, inequalities and vulnerabilities of children, youth and families in a globalised world from their specific contexts. Although the most prominent research methodology was critical literature studies, methods like autoethnographic, and empirical methods were also used. No decisions were made on a specific method of research for this publication. This publication can be viewed as an interdisciplinary and intra-disciplinary, because it deals with social sciences, anthropology, psychology, missiology, systematic theology and practical theology.